Halal food, market access and exception to WTO law: new aspects learned from Indonesia - chicken products - Ahamat, Haniff; Abdul Rahman, Nasarudin (The National Taiwan University Press and the Asian Center for WTO & International Health Law and Policy, College of Law, National Taiwan University, 2018)
Halal is the dietary law for Muslims. Complying with its rules, which are based on Islamic religious texts, is required for practicing Muslims all over the world in the context of consuming food and other consumer products. Halal measures can have an effect on trade for halal-related concerns. Halal certification is required as a condition for the importation of certain food products into some countries. These measures can be inconsistent with the World Trade Organization (hereinafter “WTO”) as shown in Indonesia — Chicken Products (2017). However, the extent to which WTO Member States are given leeway in implementing their halal measures in order for the exceptions under the WTO vis-à-vis Article XX of General Agreement on Tariffs and Trade (hereinafter “GATT”) to apply needs to be examined. Based on these premises, this paper seeks to discuss the legal issues in the GATT/WTO context arising from the halal measures. The measures will be conceptualised before the application of GATT/WTO rules to such measures is assessed. The interplay between Article XX of GATT and halal measures will be explored. This will be followed by an analysis of the decision of the WTO Panel in the Indonesia — Chicken Products case